Stars of Portent: Comets and Disasters in the Philippine Past, 1566 - 1910 - Bolata, Emmanuel Jayson V. (BANWAAN: The Philippine Journal of Folklore, 2025)
This paper shows how the perceived relationship between comets and disasters developed and deepened among the Philippine communities through time. Lexicographic data show how indigenous Filipinos thought about comets and their passing, while ethnographic and historical accounts provide a glimpse to the knowledge processes which put into reason these cometary perceptions and predictions. Ancestral tradition, historical experience, and generations of observations can be cited as causes that established and strengthened this mentality. The arrival of Spaniards in the sixteenth century, nevertheless, made these perceptions more durable and tenacious. As shown in select historical accounts, Spanish priests and soldiers possessed the popular lore of the comet-fearing West. Gradual permeation of modern science in the nineteenth and twentieth centuries combatted these “primitive superstitions” and “popular apprehensions” through an army of scientists, scholars, and schoolbook writers. However, comet astrology persisted among the Filipinos, as seen in print and folklore. The historical period covered is from 1566, when a comet was sighted in Cebu, to 1910, the year when the Halley’s Comet graced the Philippine sky. These comet apparitions marked not only the astronomical events but also the complementing and conflicting discourses they caused. Keywords: comet, disasters, ethnoastronomy, astrology, Philippine astronomy